PENGARUH PEMBERIAN KONSELING GIZI TERHADAP PEMILIHAN MAKAN PADA REMAJA PUTRI OVERWEIGHT DAN OBESITAS - Putri Maulidiyah; Ratih Kurniasari (Dian Nuswantoro Semarang, 2023)
In Indonesia there are still many adolescents who experience multiple nutritional problems caused by the increasing number of population with more nutritional status, one of which is overweight. One of the causes of overweight is because of food selection. Food choices can be influenced by family eating habits, advertisements in various media, peers, and the environment. Nutrition counseling is a form of approach that aims to help clients/respondents identify and analyze problems with clients and provide alternative solutions to problems. The purpose of this study was to see the effect of providing nutritional counseling on food choices in overweight female adolescents. The method used in this research is literature review by collecting research journals or reviewing articles by searching the database using Google Scholar as many as 4 journals spanning 2017-2022. In this study, the provision of nutritional counseling can influence and change the choice of food for young women, who initially chose random food to choose good and healthy food. Keywords: nutrition counseling; overweight; youth; food